2020
DOI: 10.1016/j.molp.2020.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the 3D Genome Architecture in Plants: Present and Future

Abstract: The eukaryotic genome has a hierarchical three-dimensional (3D) organization with functional implications for DNA replication, DNA repair, and transcriptional regulation. Over the past decade, scientists have endeavored to elucidate the spatial characteristics and functions of plant genome architecture using high-throughput chromatin conformation capturing technologies such as Hi-C, ChIA-PET, and HiChIP. Here, we systematically review current understanding of chromatin organization in plants at multiple scales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 160 publications
(200 reference statements)
4
51
0
1
Order By: Relevance
“…Hence, nCUT&Tag may be scalable for highthroughput or single-nucleus profiling of histone marks in plants. Importantly, the PAT-or PGT-mediated chromatin immunocleavage strategies may greatly facilitate the development of single-cell ligation-free 3D genome mapping technologies (Ouyang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, nCUT&Tag may be scalable for highthroughput or single-nucleus profiling of histone marks in plants. Importantly, the PAT-or PGT-mediated chromatin immunocleavage strategies may greatly facilitate the development of single-cell ligation-free 3D genome mapping technologies (Ouyang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…2004 ). However, whether these cohesins have similar functions is still unclear ( Ouyang et al. 2020 ).…”
Section: Chromosomal Architecture Featuresmentioning
confidence: 99%
“…Recent research has revealed that the information and function of a genome are not only modulated via epigenetic marks in the linear DNA sequence but also by the occupancy and three-dimensional (3D) chromatin organization within the nucleus ( Doğan and Liu 2018 , Grob 2020 ). This occupancy and 3D organization have important functional implications for DNA replication, DNA repair and transcription regulation ( Ouyang et al. 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hi-C studies of Arabidopsis , rice ( Oryza sativa ), and maize ( Zea mays ) interphase chromatin, revealed an important role of repeat content in shaping local chromatin domains ( Dong et al, 2020 ). In contrast to plants with large genomes, like rice, that exhibit TAD-like domains ( Ouyang et al, 2020 ), Arabidopsis features few domain-like structures. At the same time, rice and Arabidopsis are characterized by additional functional long-range interacting domains that may be plant-specific – inactive heterochromatic islands (IHIs) or KNOT engaged Elements (KEEs).…”
Section: Fish-visualization Of Chromatin Domains In Model Organismsmentioning
confidence: 99%